Effectiveness of Interactive Digital Media on Learning Outcomes in PBL-based Science at Elementary Schools - Khoirunnisa Khoirunnisa; Muhtar Mochamad Solihin (Jurnal Kiprah Pendidikan, 2026)
This study aims to analyze the effectiveness of interactive digital media integrated with the Problem-Based Learning (PBL) model on student learning outcomes in elementary school science education. A Systematic Literature Review (SLR) method was employed, following the PRISMA 2020 guidelines. Articles were sourced via Google Scholar and Publish or Perish for the period of 2021–2026, yielding 37 articles; of these, 31 reported complete quantitative data and were analyzed using narrative synthesis techniques. The results indicate that the majority of quantitative studies reported statistically significant positive impacts. Of these, 27 studies specifically measured cognitive learning outcomes, which improved substantially, with N-Gain scores ranging from 0.44 (medium category) to 0.804 (high category). Furthermore, based on a limited number of studies (1–5 studies for each respective variable), the integration of interactive digital media into PBL also suggested enhancements in student learning motivation (Cohen's d = 0.911), critical thinking skills, scientific literacy, and collaboration skills (p < 0.05). These positive effects were consistently observed across various media types, such as interactive quizzes (Quizizz, Wordwall), digital books (E-books, Flipbooks), presentation tools (PowerPoint, Prezi), and immersive technologies (Augmented Reality), as well as across various research designs. These findings confirm that interactive digital media within PBL consistently provides a positive impact; however, maximum effectiveness is achieved when media features align with the PBL syntax and users' technological readiness. As a note, the literature search in this study was limited to the Google Scholar database through Publish or Perish; therefore, the scope of sources and potential publication bias should be considered when interpreting the findings